REVIEW OF ISLAMIC LAW RELATING TO MOTORVEHICLE LENHDING IN BANDUNG DISTRICT - Hardi Fardiansyah; Nanda Dwi Rizkia; Muhamad Jamalih; Richard E.G.A Angkuw (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2023)
Humans as social beings are creatures that always live in society and always need the help of other people, to meet their needs together in society. Therefore, humans are always in contact with each other. 1 The relationship between one human and another human being in fulfilling needs must have clear rules between the rights and obligations of the two based on an agreement. 2 Pawn (rahn) is an agreement to hand over property by the owner as the person paying the receivables either in whole or only in part. 3 Most pawn agreements are carried out by the community in order to meet needs or help each other among those who really need them, by providing guarantees in the form of money so that they can be trusted or dependents if the person who pawned the goods cannot pay the debt